Does TP53 guard ALL genomes? - Moorman, Anthony V. (American Society of Hematology, 2014)
In this issue of Blood, Stengel et al advance our knowledge of the genomic landscape of acute lymphoblastic leukemia (ALL) by demonstrating a high frequency of TP53 mutations in specific genetic subtypes.(1)